Análise comparativa entre Poli-L-ácido láctico e Hidroxiapatita de Cálcio quanto a bioestimulação de matriz dérmica direcionada ao tratamento da flacidez cutânea - Gonçalves, Pedro Ivo Romani de Oliveira (2024)
The loss of elasticity and thinning of the skin play a crucial role in the structural changes associated with sagging. Injectable collagen stimulators are widely used to restructure the skin and soft tissues in a minimally invasive manner, without the need for energy-based procedures or surgeries. The popularity of these procedures is driven by their simplicity, effectiveness, and rapid recovery, highlighting their biocompatibility. There is believed to be a measurable difference in therapeutic efficacy when comparing Poly-L-Lactic Acid (PLLA), Calcium Hydroxyapatite (CaHa), or a combination of both in the treatment of skin laxity, specifically in increasing collagen matrix. This study conducts a single-center, open-label, randomized clinical trial with four patients. The aim is to evaluate the effects of combined injection of Poly-L-Lactic Acid (PLLA) and Calcium Hydroxyapatite (CaHa) or the individual application of each substance on the abdominal skin of patients who will undergo abdominoplasty later. The increase in collagen matrix over the course of the study was determined through analysis of sections of skin fragments stained with Hematoxylin and Eosin (HE) using stereological grid analysis under conventional low-power light microscopy. At the initial stage, patients underwent a skin biopsy 30 days before the injection of the bio-stimulators. During the intervention, patients received injections of bio-stimulators following a template map to identify specific areas for each material. Equivalent doses of PLLA and CaHa were used, both individually and in combination. A dose of saline solution was administered in a fourth area delineated by the map as an active control. All patients were reassessed on days 60 and 120 post-application, with tissue samples collected by biopsy from each treated area. Comparative histological analysis revealed a notable increase in collagen matrix density in the dermis, as well as a basophilic presentation of collagen fibers (which are typically acidophilic), especially in areas treated with CaHa (which is basophilic under HE staining), suggesting CaHa dispersion along these fibers. When injected in combination (blend), dermal tissue histology revealed an even larger bundle organization of fibers, reducing the interstitial space. An increase in the density of nuclei of cells adjacent to these bundles was also observed, indicating fibroblast proliferation. Although further studies are needed, the evaluation pointed to a statistically significant increase in collagen fibers in the treatments used, especially in the combination of biomaterials at equivalent doses